On the reconstruction of the verb “to exist” in Proto-semitic (Philology, 2024)
The current article proposes an alternative approach to Benjamin Suchard’s reconstruction of the verb *yiytaw (“to exist”) in Proto-Semitic. In his article “Proto-Semitic Existentials: *yθaw and *laθθaw”, Suchard proposes that the original meaning of this verb was “to have”, citing as its derivatives the Akkadian verbs īšu (“to have”) and the negation laššu (“does not exist”), the existential particles yēš (Biblical Hebrew) and ’īt(ay) (“exists”, Aramaic), as well as the negative verb laysa (“does not exist”, “not to be”) in Arabic. While the formal and semantic similarities make Suchard’s idea attractive, an analysis of their usage raises serious questions. This article rejects Suchard’s postulated connections and reconstructs “to exist” in Proto-Semitic as *isu, a verb from which yəhī in Biblical Hebrew and yəhwē in Aramaic are derived, both having the meaning “to be”.
Keywords: Proto-Semitic; Semitic languages; existential particles; negative existentials